Intercultural communication - Crisp, Richard J. 1973- (Critical concepts in psychology, 2015)
As research in and around intercultural communication burgeons as never before, this new four-volume collection from Routledge's acclaimed Critical Concepts in Psychology series meets the need for an authoritative reference work to make sense of a rapidly growing and ever more complex corpus of literature. Edited by a leading social psychologist, the collection is organized into four principal themes: intercultural differences; intercultural conflict; intercultural ideology; and intercultural integration. Intercultural Communication provides a one-stop 'mini library' of foundational and canonical work. The collection also includes cutting-edge analyses and discussions of theory and research, as well as major works addressing social intervention and policy implications